2011
DOI: 10.1371/journal.pone.0023040
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Controlled Feasibility Trial of an Evidence-Informed Behavioural Intervention for Obese Adults with Additional Risk Factors

Abstract: BackgroundInterventions for dietary and physical activity changes in obese adults may be less effective for participants with additional obesity-related risk factors and co-morbidities than for otherwise healthy individuals. This study aimed to test the feasibility and acceptability of the recruitment, allocation, measurement, retention and intervention procedures of a randomised controlled trial of an intervention to improve physical activity and dietary practices amongst obese adults with additional obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Forward and backward searches identified another 13 eligible publications (see Figure 1). A total of 61 comparisons (58 publications) were included for the self-efficacy analyses [18-75] and 42 comparisons (39 publications either linked to or the same as the original 58 publications) were included for the physical activity behaviour analyses [18,19,24-26,28,35,36,38,40-43],[45,47-50,52,54,56-59,61,63,65-68],[70,71,73,75-81]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward and backward searches identified another 13 eligible publications (see Figure 1). A total of 61 comparisons (58 publications) were included for the self-efficacy analyses [18-75] and 42 comparisons (39 publications either linked to or the same as the original 58 publications) were included for the physical activity behaviour analyses [18,19,24-26,28,35,36,38,40-43],[45,47-50,52,54,56-59,61,63,65-68],[70,71,73,75-81]. …”
Section: Resultsmentioning
confidence: 99%
“… a Data on age, exact BMI, gender and ethnicity was not provided by all studies. b This is the range for both the self-efficacy and physical activity studies. c This data is for the statistical analyses conducted, some of the studies were RCT’s but were analysed as pre-post studies. d One study measured perceived behavioural control, not self-efficacy [68]. …”
Section: Resultsmentioning
confidence: 99%
“…105 High levels of deprivation are known to predict poor consent rates in trials evaluating behavioural interventions for sedentary people. 106,107 It may be particularly difficult to recruit healthy participants in deprived communities for an intervention that may have significant costs to participants, including both the costs of behaviour change and the time and travel costs of attending for the intervention as well as recruitment, baseline data collection and follow-up. We were also recruiting participants from an age group (40-65 years) in which many people have both work and family responsibilities, which may make it particularly likely that perceived costs will outweigh the perceived benefits of participation.…”
Section: Recruitment and Retentionmentioning
confidence: 99%
“…11 Men are under-represented in weight loss interventions 12 and attrition is high in weight loss studies. 13,14 Previous research has identified many features of an intervention that could make it attractive to potential male participants. Convenience and compatibility with a busy life are important, [15][16][17] as is the use of community settings for intervention delivery.…”
Section: Introductionmentioning
confidence: 99%